Physiological mechanisms of vascular response induced by shear stress and effect of exercise in systemic and placental circulation - Rodríguez, Iván; González, Marcelo (Frontiers in Pharmacology, 2014)
Physiological vascular function regulation is essential for cardiovascular health and depends on adequate control of molecular mechanisms triggered by endothelial cells in response to mechanical and chemical stimuli induced by blood flow. Endothelial dysfunction is one of the main risk factors of cardiovascular pathology, where the imbalance between the synthesis of vasodilator and vasoconstrictor molecules is common in the development of vascular disorders in systemic and placental circulation. In the placenta, an organ without autonomic innervations, the local control of vascular tone is critical for maintenance of fetal growth and mechanisms that underlie shear stress response induced by blood flow are essential during pregnancy. In this field, shear stress induced by moderate exercise is one of the most important mechanisms to improve vascular function through nitric oxide (NO) synthesis and stimulation of mechanical response of endothelial cells triggered by ion channels, caveolae, endothelial NO synthase (eNOS) and vascular endothelial growth factor (VEGF), among others. The demand for oxygen and nutrients by tissues and organs, especially in placentation and pregnancy, determines blood flow parameters and physiological adaptations of vascular beds for covering metabolic requirements. In this regard, moderate exercise versus sedentarism shows potential benefits for improving vascular function associated with the enhancement of molecular mechanisms induced by shear stress. In this review, we collect evidence about molecular bases of physiological response to shear stress in order to highlight the relevance of moderate exercise-training for vascular health in adult and fetal life.